Metabolism of Xenobiotic Compounds Increases Free Radical Production and Reduces Endogenous Antioxidant Mechanisms - Saputra, I Putu Bayu Agus (Meditory : The Journal of Medical Laboratory, 2023)
Xenobiotic compounds are foreign substances that enter the body. These substances include drugs, insecticides, toluene, chloroform, formalin, and others that can enter by inhalation, through skin exposure or swallowed together with food. The use of xenobiotic compounds is increasing every year along with the development of the industrial sector, which impacts greater exposure for workers. Xenobiotic compounds that enter the body will cause harm to the body, and they will be detoxified in the liver. Xenobiotic compounds can bind to cytochrome p450 isoform 2E1, which will cause the formation of free radicals. A body exposed to xenobiotic compounds can respond by reducing free radicals using endogenous antioxidants. They are Superoxide Dismutase (SOD) and Glutathione Peroxidase (GPX). If the amount of free radicals exposure is too large, oxidative stress will occur. It triggers liver cell damage and release of alanine aminotransferase (ALT) and Aspartate Aminotransferase (AST) into the blood vessels, which causes an increase in these enzymes in the blood.